The Aesthetic Construction of Sundanese Classical Dance: From Dancer Aesthetics to Dance Aesthetics - Ria Sabaria; Agus Budiman; Ace Iwan Suryawan; Fitri Kurniati (CV. Edujavare Publishing, 2026)
Studies of dance aesthetics in Indonesia have so far been more oriented towards the performative qualities of dancers, thus failing to comprehensively explain the mechanisms of aesthetic formation of dance works. This study aims to formulate the aesthetic construction of Sundanese Classical Dance through an analysis of the relationship between artistic structure and the Sundanese aristocratic cultural value system. This study uses a qualitative paradigm with an ethnochoreological approach. Data were collected through participatory observation, in-depth interviews, documentation studies, and literature studies of dance maestros, choreographers, academics, cultural figures, and practitioners of Sundanese Classical Dance in West Java. The analysis was carried out iteratively through the identification of artistic structures, identification of cultural values, relational analysis, and conceptual synthesis. The results of the study indicate that the aesthetics of Sundanese Classical Dance are not formed solely by the individual abilities of the dancers, but are the result of a construction born from the dynamic interaction between artistic structures including movement, music, makeup, costume, spatial patterns, and presentation with the Sundanese aristocratic cultural value system such as refinement, harmony, politeness, self-control, and honor. This study produces a Sundanese Classical Dance Aesthetic Construction Model that explains the process of transforming cultural values ​​into artistic structures, thereby producing aesthetic experiences and shaping the aesthetic identity of dance works. These findings expand the study of dance aesthetics from a dancer-centered paradigm to one that positions dance works as artistic and cultural constructions and offers a conceptual framework that can be applied to research on various Indonesian dance traditions.